“Plus ça change, plus c'est la même chose”: vignettes from multinational archaeological research in Mongolia, 1995 (Studia Archaeologica, 2025)
2025 marks the 30th anniversary of the Joint Mongolian-Russian-American Archaeological Expedition (JMRAAE). Vignettes of the historical contexts of and personalities involved in the genesis of JMRAAE in 1995 provided by one of the expedition’s three founding co-directors, explain its organization, early achievements, and historical context.